Разработка и анализ двухиндексной модели распределения частотных каналов в многоканальной mesh-сети стандарта IEEE 802.11 - Гаркуша, С. В. (Проблеми телекомунікацій, 2011)
The article introduces a double index model of the distribution frequency channels in the multi-channel mesh-networking standard IEEE 802.11. The analysis of the solutions obtained using different optimality criteria.
Keywords: частотный канал; mesh-сеть; коллизия